ANALISIS IMPLEMENTASI BPJS KETENAGAKERJAAN DI PERUSAHAAN KONTRUKSI BATAM - Shofiy Shofiyah; Yuli Indah Fajar Dini (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research explores administrative and membership constraints, reporting and contribution payment complexities, BPJS benefit claim processes, and technical and service access challenges in the implementation of BPJS Ketenagakerjaan in Batam construction companies. The qualitative research method involved in-depth interviews with relevant staff. The results show that although there are obstacles such as labor fluctuations, the recording system and Jamsostek Mobile application help to overcome some of these problems. In conclusion, better understanding and efficient management can help ensure sufficient protection for employees. Suggestions include improved management systems, training, consultation with BPJS experts, and improved communication with BPJS to ease administration and claims processes. Thus, more effective implementation of BPJS Ketenagakerjaan can provide better protection for construction company employees.